2017
DOI: 10.1177/2048004016689440
|View full text |Cite
|
Sign up to set email alerts
|

Renal ischemia/reperfusion-induced cardiac hypertrophy in mice: Cardiac morphological and morphometric characterization

Abstract: BackgroundTissue remodeling is usually dependent on the deposition of extracellular matrix that may result in tissue stiffness and impaired myocardium contraction.ObjectivesWe had previously demonstrated that renal ischemia/reperfusion (I/R) is able to induce development of cardiac hypertrophy in mice. Therefore, we aimed to characterize renal I/R-induced cardiac hypertrophy.DesignC57BL/6 J mice were subjected to 60 minutes’ unilateral renal pedicle occlusion, followed by reperfusion (I/R) for 5, 8, 12 or 15 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 32 publications
1
15
0
Order By: Relevance
“…The beta growth transforming factor (TGF- β ) is one of the main regulators of NOX and has a fundamental role in the establishment of fibrosis and disease progression [ 35 , 36 ]. Despite these studies, previous data from our laboratory indicate a reduction in TGF- β gene expression in 12 and 15 days after ischemia [ 37 ]. In this way, we can suppose that the general reduction observed in NOX is due to a reduction mainly in NOX4 as a consequence of the reduction in TGF- β observed in previous studies in our laboratory.…”
Section: Discussionmentioning
confidence: 81%
“…The beta growth transforming factor (TGF- β ) is one of the main regulators of NOX and has a fundamental role in the establishment of fibrosis and disease progression [ 35 , 36 ]. Despite these studies, previous data from our laboratory indicate a reduction in TGF- β gene expression in 12 and 15 days after ischemia [ 37 ]. In this way, we can suppose that the general reduction observed in NOX is due to a reduction mainly in NOX4 as a consequence of the reduction in TGF- β observed in previous studies in our laboratory.…”
Section: Discussionmentioning
confidence: 81%
“…1D). Systemic in ammation regulates cardiac tissue structure, as distinct sections of heart tissues have different collagen content [37]. HE staining of rat myocardial tissue revealed that renal IRI induced a disordered structure, edema, and localized necrosis in myocardial cells, particularly in the IR (obese) group, combined with interstitial edema.…”
Section: Discussionmentioning
confidence: 99%
“…(AMI) induced by renal IR is indeterminate, including kidney dysfunction which results in a hyperin ammatory state and volume overload [6]. Renal IR can lead to impactful changes in heart morphology combined with increased microvasculature [7]. The study has demonstrated that the IR mechanism is closely related with mitochondrial dysfunction in heart [8].…”
mentioning
confidence: 99%
“…We used enzyme-linked immunosorbent assays to detect TNF-α and IL-1β, and our results show that renal IRI increased serum levels of TNF-α and IL-1β, particularly in the IR (obese) group, compared with the sham group (p < 0.05), which decreased after the pretreatment with TIIA, CsA, and TIIA+CsA ( Figure 1D). Systemic inflammation regulates cardiac tissue structure, as distinct sections of heart tissues have different collagen content [37].…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of acute myocardial injury (AMI) induced by renal IR is indeterminate, including kidney dysfunction which results in a hyperin ammatory state and volume overload [6]. Renal IR can lead to impactful changes in heart morphology combined with increased microvasculature [7]. The study has demonstrated that the IR mechanism is closely related with mitochondrial dysfunction in heart [8].…”
Section: Introductionmentioning
confidence: 99%